A Comprehensive Review of Celecoxib Oral Solution for the Acute Treatment of Migraine - Nazir Noor; Courtney LaChute; Mathew Root; Jasmine Rogers; Madeleine Richard; Giustino Varrassi; Ivan Urits; Omar Viswanath; Nazih Khater; Alan D. Kaye (Health Psychology Research)
A migraine is a clinical diagnosis with a presentation of one or more severe unilateral or bilateral headache(s) often preceded by an aura and typically accompanied by nausea, vomiting, photophobia, and/or phonophobia. This neurological disease is often debilitating and greatly affects the quality of life of those it inflicts. In fact, a recent study conducted by the Global Burden of Disease and published in The Lancet Neurology revealed that migraines ranked second to only back pain as the most disabling disease. Triggers for migraines have ranged from female sex, low socioeconomic status, and diet to loud noises, sleep hygiene, and stress. Along with its clinical presentation, laboratory tests and imaging help rule out other potential causes of the headache and lead to a diagnosis of migraine. Migraines are typically divided into three phases: prodromal, headache, and postdrome. The pathophysiology of each phase remains under investigation, with differing theories regarding their pathways. Existing therapies are abortive therapies for acute migraines or preventative therapies. Abortive therapy consists of NSAIDs and triptans. Preventative therapies include tricyclic antidepressants, calcium channel blockers, beta-blockers, and anticonvulsants. In this review, we focus on the role of NSAIDs and the COX-2 inhibitor, celecoxib oral solution, for the abortive treatment of acute migraines.